Effects of Pravastatin on Type 1 Diabetic Rat Heart with or without Blood Glycemic Control. (28th February 2018) - Min, Jeong Jin; Shin, Byung-Seop; Lee, Jong-Hwan; Jeon, Yunseok; Ryu, Dae Kyun; Kim, Sojin; Shin, Young Hee
Abstract : Although statins have been suggested to attenuate the progression of diabetic cardiomyopathy, its effect without glycemic control remains unclear. Therefore, we evaluated the effect of pravastatin on diabetic rat hearts according to glycemic control. Rats were randomly divided into five groups: control (C), diabetes (D), diabetes with insulin (I), diabetes with pravastatin (P), and diabetes with insulin and pravastatin (IP). Eight weeks after allocated treatments, the heart was extracted and analyzed following echocardiography. Cardiac fibrosis was measured using Masson's trichrome stain. Cardiac expression of collagen I/III, matrix metalloproteinase (MMP)-2, MMP-9, and angiotensin-converting enzyme (ACE)/ACE2 was evaluated by immunohistochemistry and/or Western blot. Enzyme-linked immunosorbent assay was used for measuring reactive oxygen species (ROS). Diabetic groups without glycemic control (D and P) showed significantly impaired diastolic function and increased levels of cardiac fibrosis, collagen I/III, MMP-2, MMP-9, and ROS production. However, there were little significant differences in the outcomes among the control and two glucose-controlled diabetic groups (I and IP). Groups C and IP showed more preserved ACE2 and lower ACE expressions than the other groups did (D, I, and P). Our study suggested glycemic control would be more important to attenuate the progression of diabetic cardiomyopathy than pravastatin medication.